A Study of Traffic Stream Characteristics on National Highway Under Heterogeneous Traffic Conditions (International Journal of Innovative Research in Engineering & Management, 2022)
The Statistical representation of the  complex traffic flow system for the cause of distinguishing  as well as forecasting the functioning of traffic is known as  Traffic flow modelling. The principal basis of several  traffic flow models is represented by traffic stream models.  Traffic stream models show us the basic interrelationship  among the three basic traffic flow variables i.e., speed of  vehicle, flow of vehicle and density of vehicles.  Interpretation of the traffic flow variables, their  interdependence and approach to model traffic are  extremely crucial in the designing, operating and planning  of transit systems. Numerous ground work research has  been done recommending various traffic stream models.  Designing of transit systems is a complex problem and  includes various key parameters like: road type, road  width, width of vehicle, Cross-section of road, Number of  lanes etc. Designing of roads takes place according to the  recommendations of Indian Road Congress. In this paper  various values obtained from observations on local data  were done involving traffic flow. The purpose of this  research is to study and examine the traffic flow on lanes  in order to explore a model which will allow continuous  movement of traffic on the National Highway. A realistic  perception of traffic flow pattern for such crucial roads is  important for traffic functioning, organizing and  administering for assuring the maximum level of service.  Using elementary framework of traffic flow for the choice  and location of selected road, width of road, sample time,  survey of traffic, video recordings of traffic, as well as  statistical inquiry and figuring of basic parameters of  traffic flow has been done. This study will be done under  the heterogeneous conditions of traffic on national  highways and the values of various traffic flow variables  will be extracted. These constants will help us in obtaining  a link between various flow parameters like vehicle  density, vehicle volume, vehicle speed etc., and in turn  help us in obtaining graphical relations between various  traffic parameters for the traffic network. This will help us  in developing the theoretical relationship between various  traffic flow variables which will in turn enable us to model  for current roads.
Keywords: Traffic Flow Modelling; Traffic Stream Modelling; Traffic Flow Characteristics; Traffic Parameters; Heterogeneous Traffic Conditions; Regression Analysis